Evaluation of the use and handling of three different pen systems considered for in vitro fertilization treatment. (December 2014) - Imthurn, Bruno; McVeigh, Enda; Stiller, Ruth; Arnold, Michelle; Pringle, Fiona; Irps, Charlotte; Rettenbacher, Manfred
<x xml:space="preserve">Abstract</x> Objective: The objective of this study was to assess and compare the features of the Bemfola, Gonal-f and Puregon injection pens. Methods: Females who intended to undergo hormonal treatment received the three different pens in a randomized, consecutive sequence. For each of the pens, the potential patients completed an Injection Pen Assessment Questionnaire, as well as a questionnaire comparing the handling, convenience and preference among the three pens. Results: The mean score on the visual analogue scale (VAS) for the Bemfola pen (BP) was 77.8 ± 14.0; for the Puregon pen (PP), 72.1 ± 12.4; and for the Gonal-f pen (GP), 68.6 ± 16.4. The BP was superior to both competitor devices in pen size, inconspicuousness, ease of use and dose changing; no significant differences to both competitor pens were observed in the way the pen looks, the way the pen feels and the ease of injection of the volume. The 'overall' assessment was significantly better for the BP when compared to the GP (p = 0.0019), while no significant difference was observed between the BP and the PP. Conclusions: This study demonstrated significantly higher ratings for pen size, inconspicuousness, ease of use and dose adjustment for the BP compared to other marketed pens.